A single-set functional training program increases muscle power, improves functional fitness, and reduces pro-inflammatory cytokines in postmenopausal women: A randomized clinical trial - Rocha, Jackson Neris de Souza; Vasconcelos, Alan Bruno Silva; Aragão-Santos, José Carlos; de Resende–Neto, Antônio Gomes; Monteiro, Marcos Raphael Pereira; Nogueira, Albernon Costa; Cardoso, Alan Pantoja; Corrêa, Cristiane Bani; Moura, Tatiana Rodrigues de; Da Silva-Grigoletto, Marzo Edir (Frontiers in Physiology, 2023)
Introduction: Aging can be associated with reduced muscle power, functional decline, and increased plasma concentrations of proinflammatory cytokines. Functional training (FT) can improve muscle power, functional fitness and reduce plasma cytokines. However, the functional training optimal volume required to produce these adaptations must be clarified. Our study analyzed the effects of multiple–set functional training (MSFT) and single–set functional training (SSFT) on postmenopausal women’s muscle power, functional fitness, and inflammatory profile. Methods: Forty–three women were randomly allocated into three groups: multiple–set functional training (n = 16, age 64.13 ± 5.17), single–set functional training (n = 14, age 63.79 ± 4.88), and control group (CG, n = 13, age 64.62 ± 5.44). The bench press and squat exercises evaluated upper and lower limb muscle power. The following tests assessed functional fitness: putting on and taking off a T–shirt, gallon–jug shelf–transfer, standing up and walking around the house, five times sit–to–stand, and 400–m walk. Plasma cytokine (TNF–α, IL–6, and IL 10) concentrations were measured by flow cytometry. Results: Single–set functional training and multiple–set functional training increased upper and lower limbs muscle power and improved functional fitness, except for the putting on and taking off a T–shirt test. Multiple–set functional training reduced TNF–α and IL–6, while single–set functional training reduced only TNF–α. IL–10 was unaffected by exercise. Discussion: Single–set functional training and multiple–set functional training, therefore, promoted similar muscle power and functional fitness improvements over 24 weeks. Multiple–set functional training was more effective than single–set functional training, reducing both TNF and IL–6, while single–set functional training only decreased TNF–α.